Hubungan Komunikasi Penyedia Layanan Kesehatan dengan Rehospitalisasi pada Pasien Congestive Heart Failure - Hidayah, Nurul; Aulia Kurniawati, Dian (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2024)
Communication is the process of conveying information, whether in the form of messages, ideas or thoughts from the communicator to the communicant. Communication plays an important role in the patient recovery process, especially Congestive Heart Failure patients. The aim of this study is to analyze the relationship between health service provider communication and rehospitalization in Congestive Heart Failure patients. This research method is quantitative research with a descriptive analysis model involving 27 Congestive Heart Failure patients during rehospitalization. The sampling technique is total sampling. The data collection tool in this research is a questionnaire containing 30 questions. Data analysis in this study used Chi Square. The results of statistical tests using Chi Square obtained a p value = 0,000 with an Odd Ratio (OR) = 9,15. So, it can be concluded that there is a relationship between communication between health service providers and rehospitalization in Congestive Heart Failure patients and respondents who have no communication with health service providers are 9,15 times more likely to undergo rehospitalization > 1 time compared to respondents who communicate with service providers. health. Suggestions for health service providers are expected to improve services, especially communication when treating Congestive Heart Failure patients in hospitals. It is hoped that this communication from health service providers can minimize the incidence of rehospitalization. Abstrak Komunikasi adalah proses penyampaian informasi, baik berupa pesan, ide atau gagasan dari komunikator kepada komunikan. Komunikasi berperan penting dalam proses kesembuhan pasien terutama pasien Congestive Heart Failure. Tujuan dari penelitian ini adalah untuk menganalisa hubungan komunikasi penyedia layanan kesehatan dengan rehospitalisasi pada pasien Congestive Heart Failure. Metode penelitian ini adalah penelitian kuantitatif dengan model analisis deskriptif yang melibatkan 27 pasien Congestive Heart Failure selama rehospitalisasi. Teknik pengambilan sampel dengan total sampling. Alat pengumpul data dalam penelitian ini berupa kuesioner yang berisi 30 pertanyaan. Analisa data pada penelitian ini menggunakan Chi Square. Hasil uji statistik dengan menggunakan Chi Square diperoleh nilai p value = 0,000 dengan Odd Ratio (OR) = 9,15. Sehingga, dapat ditarik kesimpulan bahwa terdapat hubungan komunikasi penyedia layanan kesehatan dengan rehospitalisasi pada pasien Congestive Heart Failure dan responden yang tidak ada komunikasi dengan penyedia layanan kesehatan berpeluang 9,15 kali lebih besar menjalani rehospitalisasi > 1 kali dibandingkan dengan responden yang melakukan komunikasi dengan penyedia layanan kesehatan. Saran bagi penyedia layanan kesehatan diharapkan dapat meningkatkan pelayanan terutama komunikasi pada saat perawatan pasien Congestive Heart Failure di rumah sakit. Komunikasi penyedia layanan kesehatan ini diharapkan dapat meminimalisasi kejadian rehospitalisasi. Kata kunci: Komunikasi, Congestive Heart Failure, Rehospitalisasi.